The Ancient Roman Empire and the British Empire in India : The Diffusion of Roman and English Law throughout the World: Two Historical Studies - Bryce, James (Brill | Manohar Publishers & Distributors, 2024)
This volume is primarily based on two essays, 'Roman and the British Empire' and 'Extension of Roman and English Laws throughout the World'. The first essay is a comparative study of the modern British Empire and the classical Roman Empire. This part is deals with the British and Roman attitudes towards race, military character, and strength, despotic systems followed by both empires, taxation, revenue, and administrative policies, attitude towards natives, and induction of the native population into civil services and the military, and influences of climate and geographic condition in the expansion of British and Roman Empire. The second essay deals with the issue of Roman and English laws, the Roman imperial laws, their attitude towards Indian laws, the mixture of English and Indian laws in India, and the future of Roman and British laws promulgated throughout the world. This book is for students and researchers interested in comparative politics, history, and law.